(untitled) (American Journal of Islam and Society, 1987)
Introduction . . .The enterpriser addressing a Greek who had been boasting of the scientific achievement of his people, says: You boast most unreasonably of these sciences; for you did not discover them by your own penetration, but attained them from the scientific men of Ptolemy’s times; and some sciences you took from the Eygptians in the days of Prammetichus, and then introduced them into your own land, and now you claim to have discovered them. The King asked the Greek philosopher: "Can it be as he says?" He replied saying, "It is true; we obtained most of the sciences from the preceding philosophers, as others now receive them from us. Such is the way of the world - for one people to derive benefit from another. Rasail of the Ikhwan Al-Safa Never in any age was any science discovered, but from the beginning of the world wisdom has increased gradually, and it has not yet been completed as regards this life. Roger Bacon . . .there is no longer any excuse for a pmctice which has confounded the study of medieval economics since its inception more than a century ago, namely, that of basing the most sweeping historical generalizations on a fav familiar names, with no regard for context and continuity; even the best textbooks in the field still skip and jump from one century to the next, in and out of different traditions. But a scholastic commentator superimposed his own ideas on those accumulated in the particular tmdition in which he wrote, accepted its premises and adopted its language. He cannot be fully understood until its foundation is also dug out. It is easy now to forget that those who laid the foundation of modem economics in the eighteenth century were as familiar with the accumulated ...